PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM (Studi pada Perusahaan Ritel yang Terdaftar di Bursa Efek Indonesia Periode 2012-2016) - Indira Tanjungsari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This study aims to determine and analyze the effect of financial performance on the stock price of retail companies listed in the Indonesia Stock Exchange in the period of 2012-2016. This explanatory research identifies relationship between dependent and independent variables through a hypothesis testing. Using purposive sampling method, nine of 23 retail companies listed in the Indonesia Stock Exchange are selected as the research sample. This study uses secondary data, which are analyzed using multiple regression analysis. The result of this study indicates that Current Ratio (CR) significantly and negatively affects stock price. Return On Assets (ROA), Debt to Euity Ratio (DER) and Inventory Turnover (ITO) significantly and positively affect stock price. Meanwhile, PER do not affect stock price. Keywords: current ratio, return on assets, inventory turnover, price earnings ratio, debt to equity ratio, stock price